2022
DOI: 10.1111/andr.13294
|View full text |Cite
|
Sign up to set email alerts
|

Which patient may benefit the most from penile prosthesis implantation?

Abstract: Background Penile prosthesis implantation has been associated with overall good functional outcomes. Of relevance, some patients reported higher level of satisfaction and quality of life. Aim We investigated the profile of the patients who may benefit the most from penile prosthesis implantation. Materials and methods Data from a national multi‐institutional registry of penile prostheses including patients treated from 2014 to 2017 in Italy (Italian Nationwide Systematic Inventarization of Surgical Treatment f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…These prostheses are also reported to have one of the highest patient satisfaction rates among all medically implanted devices (from 85 to 90%) and the lowest mechanical revision rate [268,[271][272][273][274][275], with more than 90% of implanted patients being able to achieve normal sexual activity with their partners [276]. Several studies have also shown that penile prosthesis implantation is particularly suitable for ED patients affected by Peyronie's disease [277] and for patients who underwent radical prostatectomy [273]. However, against the above advantages, penile prosthesis implantation is highly expensive, traumatic (cavernous tissue is irreversibly damaged by the implantation procedure), and may also present severe, although rare, complications, such as prosthesis infection, pump migration and automatic inflation, which can require a second surgery and other interventions.…”
Section: Penile Prosthesismentioning
confidence: 99%
“…These prostheses are also reported to have one of the highest patient satisfaction rates among all medically implanted devices (from 85 to 90%) and the lowest mechanical revision rate [268,[271][272][273][274][275], with more than 90% of implanted patients being able to achieve normal sexual activity with their partners [276]. Several studies have also shown that penile prosthesis implantation is particularly suitable for ED patients affected by Peyronie's disease [277] and for patients who underwent radical prostatectomy [273]. However, against the above advantages, penile prosthesis implantation is highly expensive, traumatic (cavernous tissue is irreversibly damaged by the implantation procedure), and may also present severe, although rare, complications, such as prosthesis infection, pump migration and automatic inflation, which can require a second surgery and other interventions.…”
Section: Penile Prosthesismentioning
confidence: 99%
“…An early multi-center study reported that more than 90% of patients with ED and their partners can achieve normal sexual activity after receiving penis prosthesis implantation (48). Recent study has shown that penis prosthesis implantation is particularly suitable for ED patients secondary to Peyronie's disease (49). Nevertheless, PPI is costly, traumatic, and prone to complications, such as prosthetic infection, pump migration, automatic inflation, secondary surgery, etc.…”
Section: Penile Prosthesis Implantationmentioning
confidence: 99%
“…Non-surgical treatments, which can be proposed to the affected patients, are reserved for the acute phase of PD with the aim of attenuating the course of the disease, improving sexual function and managing pain [6]. Surgical treatment is usually reserved for the chronic stage of the disease [6], even though penile prosthesis implantation can lead to favourable results even before the disease evolves into the chronic phase [25]. Currently, different non-surgical management options are available to treat the acute phase of PD.…”
Section: Peyronie's Disease (Pd)mentioning
confidence: 99%